2013
DOI: 10.1111/bph.12302
|View full text |Cite
|
Sign up to set email alerts
|

Emodin inhibits growth and induces apoptosis in an orthotopic hepatocellular carcinoma model by blocking activation of STAT3

Abstract: Background and Purpose Aberrant activation of STAT3 is frequently encountered and promotes proliferation, survival, metastasis and angiogenesis in hepatocellular carcinoma (HCC). Here, we have investigated whether emodin mediates its effect through interference with the STAT3 activation pathway in HCC. Experimental Approach The effect of emodin on STAT3 activation, associated protein kinases and apoptosis was investigated using various HCC cell lines. Additionally, we also used a predictive tumour technology t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(101 citation statements)
references
References 43 publications
7
91
3
Order By: Relevance
“…The given doses of emodin were similar with others demonstrating the significant effects in the inhibition of other cancer types [30, 59]. More experiments are required to further determine the critical role of IGFBP1 in this process using cells stable transfected with shRNA and exogenously expression vector of IGFBP1 in nude mice model.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The given doses of emodin were similar with others demonstrating the significant effects in the inhibition of other cancer types [30, 59]. More experiments are required to further determine the critical role of IGFBP1 in this process using cells stable transfected with shRNA and exogenously expression vector of IGFBP1 in nude mice model.…”
Section: Discussionsupporting
confidence: 81%
“…Luciferase-expressing A549 cells were injected subcutaneously in nude mice. Mice bearing xenografted lung tumors were treated with control or emodin [30] via intraperitoneal injection for up to 30 days, followed by intraperitoneal injection of D-luciferin. We showed that, compared to the control group, the high dose (50 mg/kg) emodin-treated mice demonstrated a significant growth-inhibitory effect as assessed by the Xenogen IVIS200 System (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emodin, an anthraquinone derivative from the root and rhizome of Rheum palmatum L., was found to have antitumor effects in several types of cancer by regulating multi-molecular targets involved in tumor growth, apoptosis and angiogenesis (16). Recent research demonstrated that emodin may inhibit growth and induce apoptosis in an orthotopic hepatocellular carcinoma model by blocking activation of signal transducer and activator of transcription 3 (17). It was also reported that emodin may suppresses migration and invasion through the modulation of C-X-C chemokine receptor type 4 expression in an orthotopic model of HCC (18).…”
Section: Discussionmentioning
confidence: 99%
“…Around one million new cases of HCC are estimated to arise every year [3] . Conventional treatments including chemotherapeutic synthetic drugs or interferons cause serious side effects [4] . Consequently, searching for new treatments and protections especially from medicinal plants provides an unlimited source for alternative strategies to alleviate and limit the HCC severity and expansion.…”
Section: Research Papermentioning
confidence: 99%